Analysis of Mutual Fund Investment Performance in the Ability to Regulate Higher Liquidity Increases in Indonesia - Azzam Fuadudin Dhiyaurrahman; Ardi Paminto; Musdalifah Azis (Ilomata International Journal of Tax and Accounting, 2023)
One indication of inclusive liquidity or vice versa is to detect investment patterns. The research method is descriptive-quantitative. The population taken is mutual funds that are selected based on the best return in 2022 and those that are publicly published in the Financial Services Authority (OJK). Following are the results of an analysis of mutual fund investment performance in the ability to regulate a higher liquidity increase in Indonesia in 2022-2023. Fixed Income Mutual Funds: Syailendra Premium mutual funds show good performance in generating relatively stable returns. However, the Trimegah Fixed Income Plan mutual fund has a poor performance with higher volatility and lower returns. Index Funds: BNP Paribas Sri Kehati Mutual Funds show good performance with high returns and controlled volatility. The Allianz SRI KEHATI Index Fund mutual fund also performed well. However, Danareksa Index Syariah Mutual Funds showed poor performance and high risk in that period. Equity Funds: Schroder Dana Prestasi Plus mutual funds provide good returns with more controlled risk compared to stock market indices as a whole. The Sucorinvest Equity Fund mutual funds show poor performance with negative returns. Money Market Mutual Funds: Indonesian Sharia Money Market Major Mutual Funds can be a minimal choice. Likewise with the Sucorinvest Sharia Money Market Fund mutual funds. So in general terms, Index Funds and Money Market Mutual Funds show better performance than Fixed Income Mutual Funds and Mutual Funds in general.